2018
DOI: 10.1093/infdis/jiy338
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin Is an Essential Component of the Host Defense Mechanism Against Clostridium difficile Intoxication

Abstract: Our data provide evidence for a specific HSA-dependent self-defense mechanism against C difficile toxins and provide an explanation for the clinical correlation between CDI severity and hypoalbuminemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 38 publications
1
48
1
2
Order By: Relevance
“…Human miniguts are derived from plucked hair form a healthy donor and contain crucial characteristics of human guts . For the transmembrane adhesion protein E‐Cadherin as well as for F‐actin, clear cytotoxic effects caused by bacterial toxins were reported . We observed that α‐defensin‐1 was able to protect the organoids from intoxication with the medically relevant combination of TcdA, TcdB, and CDT and prevented the tissue damage caused by the bacterial toxins.…”
Section: Discussionmentioning
confidence: 81%
“…Human miniguts are derived from plucked hair form a healthy donor and contain crucial characteristics of human guts . For the transmembrane adhesion protein E‐Cadherin as well as for F‐actin, clear cytotoxic effects caused by bacterial toxins were reported . We observed that α‐defensin‐1 was able to protect the organoids from intoxication with the medically relevant combination of TcdA, TcdB, and CDT and prevented the tissue damage caused by the bacterial toxins.…”
Section: Discussionmentioning
confidence: 81%
“…hypothesized that human serum albumin (HSA) could have a neutralizing effect on clostridial toxins. 117 TcdA and TcdB induced epithelial damage, particularly in the crypt-like regions of HIOs; however, HIOs incubated with toxins and HSA had reduced pathology. While the mechanism is not completely understood, the authors speculate that HSA might bind to the toxins in the bloodstream and induce conformational changes, leading to toxin autoproteolysis.…”
Section: Introductionmentioning
confidence: 89%
“…The GA module was shown to interact with a hydrophobic pocket formed by Met‐329, Phe‐309, and Phe‐326 located in Domain II of albumin . On the other hand, docking analyses conducted by di Masi et al predicted that domain II of HSA interacts with hydrophobic portions of the DD domain of Clostridium difficile toxins …”
Section: Discussionmentioning
confidence: 99%
“…36 On the other hand, docking analyses conducted by di Masi et al predicted that domain II of HSA interacts with hydrophobic portions of the DD domain of Clostridium difficile toxins. 37 Subsequently, we have successfully produced a recombinant HSA mutant Domain II with increased binding capacity to Aβ, using a phage display approach. It is expected that this HSA mutant domain will be a competent chaperone for peripheral interventions and is expected to have the least possibility of triggering immune responses.…”
Section: Discussionmentioning
confidence: 99%